Prevalence and clinical features of interstitial lung disease in patients with psoriasis - Nobuhiro Kanaji; Noriyuki Misaki; Makiko Murota; Masashi Iwata; Ryou Ishikawa; Kentaro Yamamura; Hisamu Tanaka; Naoya Yokota; Shuusuke Fujimoto; Toshiki Yajima; Hiroaki Dobashi; Hiromi Shimada; et al. (BMC Pulmonary Medicine)
Abstract Background Despite the autoimmune nature of psoriasis, the potential association between psoriasis and interstitial lung disease (ILD) remains underexplored. This study aimed to investigate the frequency and clinical features of ILD in patients with psoriasis and propose a new conceptual framework of “ILD associated with psoriasis”. Methods A retrospective analysis of 117 patients with psoriasis was conducted, excluding those without chest imaging prior to methotrexate or biologic use and those with other comorbidities leading to ILD. Results ILD was identified in 12 (10%) patients with psoriasis; 6/50 with psoriasis vulgaris and 6/65 with psoriatic arthritis. Three of 12 patients had no history of smoking. Serum Krebs von den Lungen-6 (KL-6) levels were elevated in patients with ILD compared to those in patients without ILD. The indeterminate for usual interstitial pneumonia (UIP) pattern was the most prevalent CT finding. A lung biopsy specimen from a representative case revealed equivalent indeterminate for UIP. Over a median 8.9-year observation period, ILD progressed in only 5 patients, with no cases of respiratory failure or death due to ILD progression, suggesting generally favourable prognoses. Conclusions ILD associated with psoriasis would be present, and its frequency is 10% of patients with psoriasis. We propose that chest radiography and a serum KL-6 test at the initial diagnosis of psoriasis would be useful in screening for the detection of ILD. We also recommend that a physician diagnosing ILD should carefully examine the skin findings, considering if psoriasis could be associated with ILD. Trial registration Not applicable.